An Analysis of Professionalism Influenced by Organizational Culture, Motivation, Experience, and Leadership at SDIT Mutiara Insan Sukoharjo - Praptomo, Mokhamad Sahid; Sudarwati; Istiatin (STIE Pelita Nusantara Semarang, 2026)
This study aims to determine the simultaneous (combined) and partial effects of the variables work culture, motivation, work experience, and school principal's managerial competence on the professionalism of teachers at the Integrated Islamic Elementary School (SDIT) Mutiara Insan, Sukoharjo Regency. This research uses a quantitative design. The population in this study consists of all teachers at SDIT Mutiara Insan Sukoharjo registered in the Education Primary Data (DAPODIK) of the Directorate General of Early Childhood Education, Primary Education, and Secondary Education. The sampling technique used in this study is census sampling, with sample size of 41 respondences. Data collection was conducted using questionnaires. The data analysis techniques employed include statistical analysis, namely multiple linear regression, F-test, t-test, and the coefficient of determination (Adjusted R²). The results show that both partially and simultaneously, the variables work culture, motivation, work experience, and school principal's managerial competence have a positive and significant effect on teacher professionalism. The coefficient of determination (Adjusted R²) of 0.843 indicates that these four variables can explain 84.3% of the variation in teacher professionalism, while the remaining 15.7% is influenced by other variables outside the model.